Lymphocyte-activating gene 3 expression in tumor cells predicts immune checkpoint inhibitor response in triple negative breast cancer - Kim, Ji-Yeon; Kim, Jeehyun; Cho, Eun Yoon; Park, Yeon Hee; Ahn, Jin Seok; Kim, Kyoung-Mee; Im, Young-Hyuck (Frontiers in Oncology, 2023)
Introduction Immune checkpoint inhibitor (ICI) is one of the standard treatment strategies in triple negative breast cancer (TNBC). However, the benefit of ICI with chemotherapy is limited in metastatic TNBC. In this study, we evaluated the effect of PD-L1 and LAG-3 expression on tissue microenvironment of mTNBC treated with ICI. Methods We reviewed representative formalin-fixed paraffin embedded specimens from metastatic or archival tumor tissues of TNBCs who treated with PD-1/PD-L1 inhibitors in metastatic setting. We used the Opal multiplex Detection kit with six antibodies (anti-PD-L1, anti-LAG-3, anti-CD68, anti-panCK, anti-CD8, anti-CD107a/LAMP antibody). Results We evaluated the association between LAG-3+cells and survival outcome regarding CK expression. Stromal LAG-3+/CK+ and LAG-3+/CK- cells were not associated with ICI-progression free survival(PFS) (P=0.16). However, LAG-3+ cell distributions in the tumor area impacted on ICI-PFS. A high density of LAG-3+CK+ cells was associated with shorter ICI-PFS compared with low densities of both LAG-3+CK+ and LAG-3+CK- cells (1.9 vs. 3.5 months). In addition, a high density of LAG-3+CK- cells had a relatively longer ICI-PFS compared with other groups (P=0.01). In terms of total area, the pattern of densities of LAG-3+CK+ cells and LAG-3+CK- cells were similar to those in the tumor area In addition, ICI-PFS of LAG-3+CK- and LAG-3+CK+ cell densities in the total area was equal to that in the tumor area. Discussion In conclusion, our findings revealed tumor-intrinsic LAG-3 expression was the resistance mechanism toward PD-1/PD-L1 inhibitors in mTNBCs. Multivariate analysis also suggested that LAG-3 expression in tumor cells was an independent predictive biomarker.